2019 IEEE International Conference on Blockchain (Blockchain) 2019
DOI: 10.1109/blockchain.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

A Security Reference Architecture for Blockchains

Abstract: Due to their interesting features, blockchains have become popular in recent years. They are full-stack systems where security is a critical factor for their success. The main focus of this work is to systematize knowledge about security and privacy issues of blockchains. To this end, we propose a security reference architecture based on models that demonstrate the stacked hierarchy of various threats (similar to the ISO/OSI hierarchy) as well as threat-risk assessment using ISO/IEC 15408. In contrast to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
(113 reference statements)
0
16
0
4
Order By: Relevance
“…As for the adversarial influence in DLT networks, previous studies, e.g., [6], [7], [23], [24], [25], [26], [27], have confirmed that prominent DLT solutions such as Bitcoin [28] and Ethereum [23] are vulnerable to Denial of Service, Eclipse Attacks, BGP highjacks, Man-in-the-Middle (MITM) attacks, network partitioning, etc. The consequences of adversarial influences are non-trivial and range from transaction dropping to double spending.…”
Section: Related Workmentioning
confidence: 92%
See 1 more Smart Citation
“…As for the adversarial influence in DLT networks, previous studies, e.g., [6], [7], [23], [24], [25], [26], [27], have confirmed that prominent DLT solutions such as Bitcoin [28] and Ethereum [23] are vulnerable to Denial of Service, Eclipse Attacks, BGP highjacks, Man-in-the-Middle (MITM) attacks, network partitioning, etc. The consequences of adversarial influences are non-trivial and range from transaction dropping to double spending.…”
Section: Related Workmentioning
confidence: 92%
“…In addition to high resource consumption, the process of node synchronization (i.e., bootstrapping) becomes a point of centralization, as it depends in part on a set of well known nodes that are assumed to be both available and honest. Today's client implementations rely on a list of well known addresses [6] that may not always be available or may even exhibit Byzantine behavior. One could work around the issue of unavailable seeds by manually adding bootstrap peers, but manually added nodes may also exhibit malicious behavior, making a new node vulnerable to various types of attacks, from denial of service to Eclipse attacks [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Validation and the consensus process is carried out by special peer nodes called "miners". [24], [22], [25].…”
Section: Consensusmentioning
confidence: 99%
“…since all the nodes have a replica of the ledger. Therefore, blockchain enhances the security in the network [22], [25].…”
Section: Enhanced Securitymentioning
confidence: 99%
“…This article is based on our previous work outlining the security reference architecture [10]. We substantially modify and extend it by the following:…”
mentioning
confidence: 99%